Revolutionizing HR Management: The Impact of Digital Transformation on Organizational Success and Business Sustainability - Hendro Iwan Pradipto; Umi Narimawati; M. Yani Syafei (Dinasti Publisher, 2025)
Digital transformation in human resource (HR) management has become critical to improving organizational performance and commercial sustainability. The purpose of this research is to evaluate the success of applying the Darwin Box application in human resource management at PT Bukit Muria Jaya, as well as its effects on organizational effectiveness and business sustainability. Furthermore, this study investigates disparities in views of digitalization efficacy across work roles and highlights barriers in digital transformation implementation. The study takes a quantitative approach, including survey methodologies and statistical analysis. A Likert-scale questionnaire was used to collect data from 1,241 employees, which were then evaluated with Pearson correlation tests and linear regression. The study found that using Darwin Box had a considerable impact on organizational performance, with a correlation value of r = 0.72 (p < 0.01) and a 51.8% contribution (R² = 0.518, p < 0.01). HR digitization also improves corporate sustainability, with operational efficiency being the most important aspect (39.7%). This study is unique in that it employs a thorough quantitative methodology to empirically examine the effects of HR digitization on organizational efficiency and business sustainability. These findings emphasize that HR digitization is more than just a technology breakthrough; it is a basic strategy for increasing business competitiveness. Key recommendations include improving training, upgrading technology infrastructure, and performing frequent reviews to maximize the benefits of digital transformation